The Village and National Identity in the Perspective of Social Changes - Vermishyan, Harutyun (Journal of Sociology: Bulletin of Yerevan University, 2012)
The article is represented through concentration of sociological questions which leads to the very issue of the reproduction of the national identity in the rural community in frames of the modernization processes. For observing the mentioned issue the rural-urban interrelation is analyzed as a symbolic sphere of traditional-modern interconnection. The multi-observational scheme of land-familycommunity is presented to reveal the village as a mechanism which sustains and reproduces the traditional elements of ethnic identity highlighting the importance of maintaining the agricultural way of life.